Age-related differences in diagnosis, treatment and outcome of acute coronary syndromes: results from the German ALKK registry - Rittger, Harald; Hochadel, Matthias; Zahn, Ralf; Senges, Jochen (EuroIntervention, 2012)
The Official Journal of EuroPCR and the European Association of Percutaneous Cardiovascular Interventions (EAPCI)